Lightweight bubble soil synergistically modified by stone powder and nano material and preparation method of lightweight bubble soil
By leveraging the synergistic effect of composite alkali activators and nanoparticle stabilizers, the activity and foam stability of stone powder are enhanced, resulting in the preparation of lightweight aerated soil with high stone powder content. This solves the problems of low stone powder activity and unstable foam, achieving lightweight aerated soil with high strength, low density, and environmental benefits.
Patent Information
- Application Number
- CN202511410872.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-29
- Publication Date
- 2026-01-09
AI Technical Summary
In existing technologies, stone powder has low chemical activity, which leads to a decrease in the mechanical strength of foamed lightweight soil. Traditional foaming agents are unstable and it is difficult to achieve a balance between low density and high strength. Furthermore, the amount of stone powder added is limited.
A composite alkali activator and nanoparticle stabilizer are used to synergistically modify aerated lightweight soil. By adjusting the ratio of cementitious materials with stone powder, water, foaming agent and nano silica, stable foam is formed and the activity of stone powder is improved, thus achieving aerated lightweight soil with high stone powder content and high performance.
With a stone powder content as high as 30%, the material's 28-day compressive strength exceeds 2.5 MPa, foam stability is significantly improved, pore structure is uniform, material density is low, impermeability and durability are enhanced, construction performance is excellent, and it is economical and environmentally friendly.
Smart Images

Figure CN121292892A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of civil engineering materials technology, specifically relating to a method for preparing aerated lightweight soil synergistically modified with stone powder and nanomaterials. Background Technology
[0002] Foamed lightweight soil has been increasingly widely used in civil engineering projects such as roadbed filling and soft soil foundation treatment due to its advantages of being lightweight, high-strength, heat-insulating, and environmentally friendly. Stone processing generates a large amount of stone powder waste, which occupies land and pollutes the environment when stockpiled. Using stone powder as an admixture in foamed lightweight soil can achieve resource utilization of solid waste and reduce material costs.
[0003] However, existing technologies suffer from the following major problems: First, stone powder itself has low chemical activity. Directly replacing cement in large quantities would significantly reduce the mechanical strength of foamed lightweight soil, severely limiting the increase in stone powder content and the expansion of its application range. Second, the foam produced by traditional foaming agents has problems such as large bubble size and uneven distribution, and insufficient stability in alkaline cement paste. The foam is prone to breakage and coalescence, resulting in uneven pore size and numerous interconnected pores in the hardened material, thus affecting its mechanical properties and durability. Finally, although adding stone powder can reduce costs, it often comes at the expense of material performance. Currently, there is a lack of an integrated technology that can systematically and synergistically activate stone powder activity and stabilize foam, making it difficult to achieve a good balance between low density and high strength.
[0004] Therefore, how to achieve both high stone powder content and high performance without significantly increasing costs is a technical challenge that urgently needs to be solved in this field. Summary of the Invention
[0005] The purpose of this invention is to provide a method for preparing lightweight aerated soil that is synergistically modified with stone powder and nanomaterials, which can synergistically improve the activity and foam stability of stone powder, achieve high stone powder content (up to 30%), and at the same time have low density, high strength and high environmental benefits, thereby solving at least one of the technical problems involved in the background art.
[0006] To solve the above-mentioned technical problems, the present invention is implemented as follows: This invention provides a synergistic modification of aerated lightweight soil with stone powder and nanomaterials, comprising the following raw materials in parts by mass: Cementitious material: 100 parts; Stone powder: 10-30 parts; Water: 35-45 parts, based on the total mass of cementitious materials and stone powder; Foaming agent: 0.5 parts; Compound alkali activator: 1.0–2.5 parts; Nanoparticle stabilizer: 0.5–2.0 parts; The composite alkali activator is composed of sodium hydroxide and water glass in a mass ratio of (0.5-1.5):1. The nanoparticle stabilizer is composed of hydrophilic nano-silica and hydrophobic nano-silica in a mass ratio of (1:3) to (3:1).
[0007] Optionally, the cementing material is ordinary Portland cement.
[0008] Optionally, the stone powder is waste generated during industrial ore mining or processing.
[0009] Optionally, the modulus of the water glass is 2.2 to 3.4.
[0010] This invention also provides a method for preparing the aforementioned stone powder and nanomaterial synergistic modification of bubble lightweight soil, comprising the following steps: Slurry preparation: Dry mix the cementitious materials, stone powder, and composite alkali activator evenly, add most of the water, and stir at high speed to form an alkali-activated matrix slurry; Foam preparation: The foaming agent, hydrophilic nano-silica, hydrophobic nano-silica and the remaining water are mixed and foamed by a physical foaming machine to generate stable foam; Mixing and casting: The stabilized foam is added to the alkali-activated matrix slurry and mixed evenly at low speed to form a fluid slurry; Curing: Pour the fluid slurry into the mold, let it stand to harden, then demold and cure according to standard until the specified age.
[0011] Optional, standard maintenance conditions are a temperature of 20±2℃ and a humidity greater than 95%.
[0012] Optionally, the nanoparticle stabilizer is added during the foaming stage.
[0013] Optionally, the amount of composite alkali activator added is 1.0% to 5.0% of the mass of the cementitious material.
[0014] Optionally, the total amount of nanoparticle stabilizer added is 0.1% to 2.5% of the mass of the cementitious material.
[0015] Compared with existing technologies, the stone powder and nanomaterial synergistic modification of bubble lightweight soil and its preparation method provided by the present invention have the following significant beneficial effects: (1) Significantly improved mechanical properties: Through the efficient activation of stone powder activity by composite alkali activator, it is transformed from an inert filler into an active cementitious component. With the synergistic effect of the optimized pore structure of nano-SiO2, the compressive strength of the material can still exceed 2.5MPa after 28 days when the stone powder content is as high as 30%. Compared with the untreated control group, the strength improvement is more than 100%.
[0016] (2) The stability of foam is greatly improved: the synergistic stabilizing effect of hydrophilic and hydrophobic nano silica particles significantly prolongs the half-life of pre-made foam, reduces foam loss during the casting process, and ultimately enables the hardened body to form an excellent pore structure with small pore size, uniform distribution and low proportion of interconnected pores, which not only improves the strength, but also enhances the impermeability and durability of the material.
[0017] (3) The synergistic effect is prominent and the technology is irreplaceable: The examples and comparative examples prove that the composite alkali activator and the nano foam stabilizer are both indispensable. The former solves the core problem of stone powder activity, while the latter provides the key guarantee for foam stability. The combination of the two produces a synergistic effect of "1+1>2", which is the key to achieving high performance under high stone powder content.
[0018] (4) Outstanding economic and environmental benefits: The amount of stone powder can be up to 30% of the cement mass (accounting for more than 50% of solid raw materials), which greatly reduces the amount of cement used and lowers the material cost. At the same time, a large amount of industrial waste stone powder is consumed, which reduces the energy consumption and carbon dioxide emissions brought about by cement production, and has significant environmental and economic benefits.
[0019] (5) Excellent construction performance: The freshly mixed slurry has good fluidity, high foam stability, is not easy to collapse, and is easy to pump and pour on site, with good engineering applicability. Attached Figure Description
[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort, wherein: Figure 1 The preparation flow chart of the method for preparing gaseous lightweight soil synergistically modified by stone powder and nanomaterials provided by the present invention is shown. Detailed Implementation
[0021] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0022] This invention provides a synergistic modification of aerated lightweight clay with stone powder and nanomaterials, comprising the following raw materials in parts by mass: Cementitious material: 100 parts; Stone powder: 10-30 parts; Water: 35-45 parts, based on the total mass of cementitious materials and stone powder; Foaming agent: 0.5 parts; Compound alkali activator: 1.0–2.5 parts; Nanoparticle stabilizer: 0.5–2.0 parts; The composite alkali activator is composed of sodium hydroxide and water glass in a mass ratio of (0.5-1.5):1. The nanoparticle stabilizer is composed of hydrophilic nano-silica and hydrophobic nano-silica in a mass ratio of (1:3) to (3:1).
[0023] In one specific embodiment, the cementing material is ordinary silicate cement. The stone powder is waste generated during industrial ore mining or processing. The modulus of the water glass is 2.2 to 3.4.
[0024] See also Figure 1 As shown, the present invention also provides a method for preparing the aforementioned stone powder and nanomaterial synergistic modification of bubble lightweight soil, comprising the following steps: Slurry preparation: Dry mix the cementitious materials, stone powder, and composite alkali activator evenly, add most of the water, and stir at high speed to form an alkali-activated matrix slurry; Foam preparation: The foaming agent, hydrophilic nano-silica, hydrophobic nano-silica and the remaining water are mixed and foamed by a physical foaming machine to generate stable foam; Mixing and casting: The stabilized foam is added to the alkali-activated matrix slurry and mixed evenly at low speed to form a fluid slurry; Curing: The fluid slurry is poured into the mold, allowed to stand and harden, then demolded and cured according to standard conditions until the specified age. The standard curing conditions are a temperature of 20±2℃ and a humidity greater than 95%.
[0025] It should be noted that the nanoparticle stabilizer is added during the foaming stage, and the total amount of nanoparticle stabilizer added is 0.1% to 2.5% of the mass of the cementitious material.
[0026] The amount of composite alkali activator added is 1.0% to 5.0% of the mass of the cementitious material.
[0027] The following detailed description of the stone powder and nanomaterial synergistic modification of bubble lightweight soil prepared according to the present invention is provided with specific embodiments and comparative examples.
[0028] Example 1 This embodiment 1 provides a method for preparing bubble-filled lightweight soil that is synergistically modified by stone powder and nanomaterials.
[0029] Raw material ratio: 210g cement, 90g stone powder (accounting for 42.9% of the cement mass), 105g water, 15g foaming agent, composite alkali activator (composed of 1.0g sodium hydroxide and 2.0g water glass with a modulus of 2.2~3.4), and 3.2g nanoparticle stabilizer (of which hydrophilic nano silica and hydrophobic nano silica each account for 1.6g, with a mass ratio of 1:1).
[0030] Preparation method: Step 1, Slurry preparation: Add 210g of cement, 90g of stone powder, 1.0g of sodium hydroxide and 2.0g of water glass to a mixer and dry mix evenly to form a dry mix. Then add most of the total water (105g) (about 90g) and stir at high speed to form a uniform alkali-activated matrix slurry.
[0031] Step 2, foam preparation: Mix 15g of foaming agent, 1.6g of hydrophilic nano silica, 1.6g of hydrophobic nano silica with the remaining 15g of water, and foam using a physical foaming machine to generate stable foam rich in nanoparticles.
[0032] Step 3, Mixing and Pouring: Slowly add all the stable foam obtained in Step 2 to the base slurry obtained in Step 1, and mix evenly using a low-speed stirring method to form a fluid foam lightweight soil slurry.
[0033] Step 4, Curing: Pour the mixed slurry into the test mold, let it stand and harden for 24 hours, then demold it and place it under standard curing conditions (temperature 20±2℃, humidity >95%) for 28 days.
[0034] Step 5, performance test: The wet density of the foamed lightweight soil was measured to be 0.667 g / cm³, and the compressive strength after 28 days reached 2.47 MPa.
[0035] Example 2 The only difference between Example 2 and Example 1 is the ratio of the nanoparticle stabilizer.
[0036] Raw material ratio: 210g cement, 90g stone powder, 105g water, 15g foaming agent, composite alkali activator (1.0g NaOH + 2.0g water glass), 3.2g nanoparticle stabilizer (where the mass ratio of hydrophilic nano silica to hydrophobic nano silica is 3:1).
[0037] The preparation method is the same as in Example 1.
[0038] Performance testing: The wet density of the foamed lightweight soil was measured to be 0.661 g / cm³, and the compressive strength after 28 days reached 2.54 MPa.
[0039] Example 3 Example 3 illustrates the performance at a medium stone powder content.
[0040] Raw material ratio: 255g cement, 45g stone powder (17.6% of cement mass), 105g water, 15g foaming agent, composite alkali activator (1.0g NaOH + 2.0g water glass), 3.2g nanoparticle stabilizer (hydrophilic NS: hydrophobic NS = 1:1).
[0041] The preparation method is the same as in Example 1.
[0042] Performance testing: The wet density of the foamed lightweight soil was measured to be 0.810 g / cm³, and the compressive strength after 28 days reached 2.92 MPa.
[0043] Comparative Example 1 Comparative Example 1 is used to illustrate the effects of not using the technical solution of this invention.
[0044] Raw material ratio: 210g cement, 90g stone powder, 105g water, 15g foaming agent. No compound alkali activator or nanoparticle stabilizer is added.
[0045] Preparation method: After dry mixing cement and stone powder, water is added and stirred into a slurry. Then ordinary foam made of foaming agent and water is added, mixed, and then poured and cured.
[0046] Performance testing: The wet density was measured to be approximately 0.65 g / cm³, the 28-day compressive strength was only approximately 1.10 MPa, and the foam stability was poor with uneven pore size.
[0047] Comparative Example 2 Comparative Example 2 is used to illustrate the effect of using the compound alkali activator alone.
[0048] Raw material ratio: 255g cement, 45g stone powder, 105g water, 15g foaming agent, composite alkali activator (1.0g NaOH + 2.0g water glass). No nanoparticle stabilizer added.
[0049] The preparation method is the same as that of Comparative Example 1.
[0050] Performance testing: The wet density was measured to be 0.810 g / cm³, and the 28-day compressive strength was 2.92 MPa. However, the stability of the freshly mixed foam was poor, and the uniformity of the pore structure of the hardened body was also poor.
[0051] Comparative Example 3 Comparative Example 3 is used to illustrate the effect of using nanoparticle stabilizers alone.
[0052] Raw material ratio: 240g cement, 60g stone powder (25% of cement mass), 105g water, 15g foaming agent, 2.4g nanoparticle stabilizer (hydrophilic NS: hydrophobic NS = 1:1). No composite alkali activator is added.
[0053] The preparation method is the same as in Example 1.
[0054] Performance Testing: The wet density was measured to be approximately 0.76 g / cm³, and the 28-day compressive strength was 2.39 MPa. While the strength was better than Comparative Example 1, it was significantly lower than Examples 1 and 2, which used both a composite alkali activator and nanoparticles at similar stone powder dosages. This demonstrates the positive effect of nanoparticles on foam stabilization and reinforcement. However, its strength was still significantly lower than Examples 1 and 2, which used both a composite alkali activator and nanoparticles at similar stone powder dosages. This indicates that without the alkali activator to activate the stone powder's activity, even with improved foam stability, the stone powder primarily acts as an inert filler, failing to fully realize its gelling potential, resulting in the final strength not reaching the optimal level. This comparison highlights the crucial and irreplaceable role of the composite alkali activator in releasing the activity of stone powder and improving the system strength.
[0055] The comparison results of the above embodiments and comparative examples fully demonstrate that the present invention, through the combined effect of composite alkali activator and hydrophilic-hydrophobic nanoparticle synergistic foam stabilization system, successfully achieved the goal of preparing high-performance foamed lightweight soil with high stone powder content. Its technical effect far exceeds that of the untreated benchmark group and is also significantly better than the comparative group using a single technical means.
[0056] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Unless otherwise specified, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes that element.
[0057] Furthermore, it should be noted that the scope of the methods and systems in the embodiments of the present invention is not limited to performing functions in the order shown or discussed, but may also include performing functions substantially simultaneously or in the reverse order, depending on the functions involved. For example, the described methods may be performed in a different order than described, and various steps may be added, omitted, or combined. In addition, features described with reference to certain examples may be combined in other examples.
[0058] The embodiments of the present invention have been described above. However, the present invention is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many other forms under the guidance of the present invention without departing from the spirit and scope of the claims, and all of these forms are within the protection scope of the present invention.
Claims
1. A type of lightweight aerated soil synergistically modified with stone powder and nanomaterials, characterized in that, The following ingredients are included in the formula according to their mass proportions: Cementitious material: 100 parts; Stone powder: 10-30 parts; Water: 35-45 parts, based on the total mass of cementitious materials and stone powder; Foaming agent: 0.5 parts; Compound alkali activator: 1.0–2.5 parts; Nanoparticle stabilizer: 0.5–2.0 parts; The composite alkali activator is composed of sodium hydroxide and water glass in a mass ratio of (0.5-1.5):
1. The nanoparticle stabilizer is composed of hydrophilic nano-silica and hydrophobic nano-silica in a mass ratio of (1:3) to (3:1).
2. The stone powder and nanomaterial synergistic modification of bubble-filled lightweight soil according to claim 1, characterized in that, The cementing material is ordinary Portland cement.
3. The stone powder and nanomaterial synergistic modification of bubble-filled lightweight soil according to claim 1, characterized in that, The stone powder is a waste material generated during the mining or processing of industrial ore.
4. The stone powder and nanomaterial synergistic modification of bubble-filled lightweight soil according to claim 1, characterized in that, The modulus of the water glass is 2.2 to 3.
4.
5. A method for preparing synergistically modified aerated lightweight soil by stone powder and nanomaterials as described in any one of claims 1 to 4, characterized in that, Includes the following steps: Slurry preparation: Dry mix the cementitious materials, stone powder, and composite alkali activator evenly, add most of the water, and stir at high speed to form an alkali-activated matrix slurry; Foam preparation: The foaming agent, hydrophilic nano-silica, hydrophobic nano-silica and the remaining water are mixed and foamed by a physical foaming machine to generate stable foam; Mixing and casting: The stabilized foam is added to the alkali-activated matrix slurry and mixed evenly at low speed to form a fluid slurry; Curing: Pour the fluid slurry into the mold, let it stand to harden, then demold and cure according to standard until the specified age.
6. The preparation method according to claim 5, characterized in that, The standard maintenance conditions are a temperature of 20±2℃ and a humidity greater than 95%.
7. The preparation method according to claim 5, characterized in that, The nanoparticle stabilizer is added during the foaming stage.
8. The preparation method according to claim 5, characterized in that, The amount of composite alkali activator added is 1.0% to 5.0% of the mass of the cementitious material.
9. The preparation method according to claim 5, characterized in that, The total amount of nanoparticle stabilizer added is 0.1% to 2.5% of the mass of the cementitious material.